Addressing matrix effects in ligand-binding assays through the use of new reagents and technology. (April 2014) - Chilewski, Shannon D; Mora, Johanna R; Gleason, Carol; DeSilva, Binodh
Background: Ligand-binding assays (LBAs) used in the quantification of biotherapeutics for pharmacokinetic determinations rely on interactions between reagents (antibodies or target molecule) and the biotherapeutic. Most LBAs do not employ an analyte extraction procedure and are susceptible to matrix interference. Here, we present a case study on the development of a LBA for the quantification of a PEGylated domain antibody where matrix interference was observed. The assay used to support the single ascending dose study was a plate-based electrochemiluminescent assay with a lower limit of quantification of 80 ng/mL. To meet sensitivity requirements of future studies, new reagents and the Gyrolab™ Workstation were evaluated.Results: Assay sensitivity improved nearly threefold in the final method utilizing new antibody reagents, a buffer containing blockers to human anti-animal antibodies, and the Gyrolab Workstation.Conclusion: Experimental data indicate that all factors changed played a role in overcoming matrix effects.